2001
DOI: 10.1152/ajprenal.2001.280.2.f356
|View full text |Cite
|
Sign up to set email alerts
|

Pendrin: an apical Cl/OH/HCO3exchanger in the kidney cortex

Abstract: The identities of the apical Cl−/base exchangers in kidney proximal tubule and cortical collecting duct (CCD) cells remain unknown. Pendrin (PDS), which is expressed at high levels in the thyroid and its mutation causes Pendred's syndrome, is shown to be an anion exchanger. We investigated the renal distribution of PDS and its function. Our results demonstrate that pendrin mRNA expression in the rat kidney is abundant and limited to the cortex. Proximal tubule suspensions isolated from kidney cortex were highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
240
2
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(254 citation statements)
references
References 35 publications
6
240
2
3
Order By: Relevance
“…Cl Ϫ /HCO 3 Ϫ exchange function in the human colon and ileum has been attributed to the protein DRA (14,15). Pendrin is expressed in the thyroid gland (54), ear (55), and kidney (16). Expression in HEK293 cells demonstrated that Pendrin can function as a Cl Ϫ /OH Ϫ , Cl Ϫ / HCO 3 Ϫ , and Cl Ϫ /formate exchanger (16).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Cl Ϫ /HCO 3 Ϫ exchange function in the human colon and ileum has been attributed to the protein DRA (14,15). Pendrin is expressed in the thyroid gland (54), ear (55), and kidney (16). Expression in HEK293 cells demonstrated that Pendrin can function as a Cl Ϫ /OH Ϫ , Cl Ϫ / HCO 3 Ϫ , and Cl Ϫ /formate exchanger (16).…”
Section: Figmentioning
confidence: 99%
“…A truncated form of human AE1 beginning at methionine 66 is found in kidney (10). Other plasma membrane anion exchange proteins include AE2 and AE3 and recently identified AE4, DRA (down-regulated in adenoma), and Pendrin (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Pendrin consists of 780 amino acids with a predicted cytoplasmic amino terminus and 12 transmembrane spanning regions (1,2). Functional studies show that pendrin mediates electroneutral exchange of Cl 2 with various anions including I 2 , HCO 3 2 , OH 2 , NO 3 2 , SCN 2 (thiocyanate), and HCO 2 2 (formate) (2)(3)(4)(5)(6)(7)(8). In addition to the inner ear and thyroid, pendrin is expressed in the kidney, airways, and adrenal gland (1,4,6,7,(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…In the thyroid pendrin is expressed on the apical membrane of follicular cells, where it facilitates I 2 efflux into the follicle colloid for thyroid hormone synthesis (2,15). In the kidney pendrin is expressed in the apical plasma membrane of type B and non-A/non-B intercalated cells, where it facilitates Cl 2 absorption and HCO 3 2 secretion, ABBREVIATIONS: ASL, airway surface liquid; CaCC, calcium-activated chloride channel; CF, cystic fibrosis; CFBE, human cystic fibrosis bronchial epithelial; CFTR, cystic fibrosis transmembrane conductance regulator; ENaC, epithelial sodium channel; EYFP-HIF, enhanced yellow fluorescent protein-H148Q/I152L/F46L; FRT, Fischer rat thyroid; HBE, human bronchial epithelial; IC 50 , drug concentration causing 50% inhibition; I sc , short-circuit current; PCL, periciliary layer; UCSF, University of California, San Francisco; YFP, yellow fluorescent protein although kidney abnormalities are rare in Pendred syndrome (4,6,16).…”
mentioning
confidence: 99%
“…Along with cystic fibrosis transmembrane conductance regulator (CFTR) and NBCe1-B, DRA may play a critical role in the secretion of HCO 3 -by the pancreatic duct. Pendrin, which is related to DRA and functions as a Cl-formate exchanger [40], may also transport HCO 3 - [41]. …”
Section: Other Hco 3 -Transportersmentioning
confidence: 99%